Analisis Faktor yang Mempengaruhi Loyalitas Karyawan melalui Kepuasan Kerja sebagai Variabel Mediasi pada LYD Group Bali - Anjivani, Kadek Sri (IPM2KPE, 2025)
This study aims to analyze the effect of Person Job Fit, Person Organizational Fit, Perceived Supervisor Support, and Work Environment on Employee Royalty (employee loyalty) at LYD Group Bali, with Job Satisfaction as a mediating variable. Data were obtained from 89 employees through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with the PLS method and bootstrapping technique. The results showed that all independent variables had a positive and significant effect on Employee Royalty, both directly and indirectly through Job Satisfaction. These findings indicate that increasing job and organizational fit, supervisor support, and a conducive work environment, through job satisfaction, can strengthen employee loyalty. The practical implication is that companies need to maintain supervisor support and focus on improving Person Job Fit to increase employee retention and loyalty. Keywords: Employee Loyalty (Employee Royalty), Job Satisfaction, Person Job Fit, Person Organizational Fit, Perceived Supervisor Support